Weldability and joining characteristics of AISI 430/AISI 1040 steels using keyhole plasma arc welding - Teker, Tanju; Ozdemir, Niyazi (Springer London Ltd, 2012)
AISI 430 and AISI 1040 steel couples were welded using the keyhole plasma-transferred arc (KPTA) welding process. Welded joints were manufactured using three different traverse speeds (0.01, 0.02 and 0.03 m/min) under three different welding currents (130, 135 and 140 A) at a constant plasma gas flow rate (1.1 l/min) and a shielding gas rate (25 l/min). In order to determine the microstructural changes that occurred, the interface regions of the welded specimens were examined by Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) and Energy Dispersive Spectrometry (EDS) after KPTA welding. Microhardness, V-notch Charpy and tensile tests were conducted to determine the mechanical properties of the welded specimens.
Keywords: Keyhole welding; Microstructure; Mechanical properties